An Explorative Literature Review of The Influence of Physical Exercises on Bone Mineral Density - Iulian È˜tefan, Holubiac (Arena-Journal of Physical Activities, 2020)
Introduction: With age, bone mineral density decreases, and as a result the risk of fracture increases. It is known that practicing physical exercises helps maintain or increase bone mineral density in both men and women. ï¿½ï¿½ï¿½ï¿½ï¿½ï¿½ï¿½ï¿½ï¿½ï¿½Fractures resulting from osteoporosis become increasingly common in women after age 55 years, resulting in substantial bone-associated morbidities, and increased mortality and health-care costs. Physical exercises stimulates the bone and it adapts to the applied mechanical forces, stimulating the obsteoblast and inhibiting osteoclast formation and activity. Purpose: The purpose of this study is to highlight the benefits of physical exercise on bone cells and bone mineral density, respectively. Methods: We searched Science Direct, Springer Link, Web of Science and PubMed for articles and reviews in the English language pusblished between 2000 and 2020, although older references were also used when appropriate. The following terms were used to give as broad range of studies as possible: , osteoporosisâ€, , bone densityâ€, , bone massâ€, , physical exerciseâ€, , strength trainingâ€, , osteoblastâ€, , osteoclastâ€, , bone physiologyâ€. Results: We limited the search to the following study designs: controlled clinical trials, guidelines, meta-analyses, systematic reviews and randomised controlled trials. Of all the articles found, we selected 98 scientific articles from which we selected the most conclusive information. Conclusion: In conclusion, we recommend practicing physical exercises from childhood, since numerous studies carried out in young, adults and in the elderly demonstrate the beneficial effects of physical exercise on bone cells, especially on osteoblasts.